EDUKASI PENCEGAHAN STUNTING MELALUI PROGRAM SOSIALISASI CUCI TANGAN DI SPS TAAM AL-IKHLAS - Amanda Putri, Fadya (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2024)
This Community Service Program or KKN is a form of community service activity which is an embodiment of the Tri Dharma of Higher Education. The KKN theme that we chose is The Important or Students Concerned about Stunting. From this theme, we chose to carry out a work program in the form of hand washing education because personal hygiene is one of the factors that can cause stunting to attack children. We target this education or counseling on hand washing at an early age because we realize that maintaining personal hygiene needs to be instilled as early as possible. In addition, by maintaining personal hygiene they not only prevent stunting but also from various other diseases. Therefore, we chose the location to implement this program, namely SPS TAAM AL-IKHLAS. The implementation method is carried out with lectures and demonstrations because we believe children will quickly understand if given examples or practiced directly.